2019
DOI: 10.3390/medicina55050209
|View full text |Cite
|
Sign up to set email alerts
|

Burnout Syndrome in Physicians—Psychological Assessment and Biomarker Research

Abstract: Background and objectives: Burnout is a syndrome typically occurring in work environments with continuous and chronic stress. Physicians are at increased risk for burnout, as a result of 24-h work, delayed work–life balance gratification, and the challenges associated with patient care. The aim of the present study was to evaluate the psychological parameters of burnout symptoms in relation to biomarkers of stress among physicians with different medical specialties. Materials and methods: A total of 303 physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 44 publications
2
29
0
2
Order By: Relevance
“…Each time, when rats where treated with Prednison, regardless the diet (obesogenic or standard), dysglycaemia and dyslipidemia were present (Table 2). Our results are in accordance with clinical studies which demonstrated that there is a negative correlation between cortisol and cholesterol/HDLc ratio and a positive correlation between saliva cortisol and fasting glycaemia and between Dexamethasone treatment and high glycaemia [19][20][21].…”
Section: Resultssupporting
confidence: 92%
“…Each time, when rats where treated with Prednison, regardless the diet (obesogenic or standard), dysglycaemia and dyslipidemia were present (Table 2). Our results are in accordance with clinical studies which demonstrated that there is a negative correlation between cortisol and cholesterol/HDLc ratio and a positive correlation between saliva cortisol and fasting glycaemia and between Dexamethasone treatment and high glycaemia [19][20][21].…”
Section: Resultssupporting
confidence: 92%
“…Based on the study findings, we suggest a stepwise approach that identifies the predictors of burnout components (EE, DP, and PA), selects the most vulnerable job category based on the identified predictors, and then manages the target job category, preferentially improving predictors that can exert a favorable influence on other job categories. We also suggest that follow-up studies should identify biomarkers and somatization in the workforce responding to infectious diseases by referring to the psychosomatic symptoms of burnout [ 64 ], biomarkers such as salivary cortisol, or biochemical parameters such as HbA1C [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…28 In addition, markers of abnormal glucose metabolism are found in physicians with symptoms of burnout. 29 A roughly twofold increase in the rate of new employment disability was found in individuals with ERI among over 40,000 workers followed for 3 years. 30 Effort-reward imbalance has been associated with increased risk of coronary events in secondary 31 and, more recently, in primary event populations.…”
Section: Scope and Impact Of Physician Burnoutmentioning
confidence: 95%